(untitled) - Shapiro, Alan C. (New Jersey, 1996)
The book provides a conceptual framework with which the key financial decisions of the multinational firm can be analyzed. The approach is to treat international financial management as a natural and logical extension of the principles learned in the foundations course in financial management. Thus, it builds on and extends the valuation framework provided by domestic corporate finance to account for dimensions unique to international finance
Keywords: Finance,Managerial economics